My Life is Now Yours - Singhi, Mannat (Research and Humanities in Medical Education, 2017)
A medical student narrates a tale of two young girls - both struggling with pulmonary tuberculosis. The story highlights the consequences of social inequity especially how it impacts healthcare and health outcomes. It also addresses the impact of the disease on the sufferer, an impact that goes beyond the mere physical, and continues even after cure is achieved.